Transforming higher education through Universal Design for Learning : an international perspective - BRACKEN (Sean); Bracken, Sean; Novak, Katie (London: Routledge, 2019)
"Providing insight into the background, theory and practical applications of Universal Design for Learning (UDL) in the Higher Education sector; this book examines and shares best practice in UDL implementation worldwide to provide institutions with strategies to increase accessibility and engagement. Every chapter provides a different perspective of how UDL has helped meet the needs of all students to ensure that education is accessible, culturally responsive, and socially just. Educational leaders and researchers across the globe assist in making this publication a crucial read for those who want to make a positive difference in Higher Education provision and outcomes"--
Introduction: Universal Design for Learning: a global framework for realizing inclusive practice in higher education -- Universal Design for Learning: license to learn: a process for mapping a Universal Design for Learning process on to campus learning -- From national policy to university practice: developing an inclusive learning environment within and beyond the United Kingdom -- Universal Design for Learning and strategic leadership: a whole university approach to inclusive practice -- Transforming the professor: motivating university students in every discipline through design -- The transition to higher education: applying university design for learning to support student success -- Using professional learning communities to redesign learning environments in HEIs -- Instructional design with UDL: addressing learning variability in college courses -- UDL in apprenticeships and career training programs that serve youth with untapped talent -- Pedagogy of seasons and UDL: the multiple temporalities of learning involving the university as a whole -- Not just disability: getting traction for UDL implementation with international students -- Transforming teaching and learning in HEIs: impacts of UDL on professional development of university lecturers -- Cognitive accessibility: stretching the boundaries of UDL in higher ed -- From teaching content to teaching students: UDL as a vehicle for improving curriculum and praxis design -- Integration through collaboration: building strategic faculty partnerships to shift minds and practices -- Creating synergies between UDL and core principles of the European higher education area in planning for pre-service teacher education -- Developing assessment and feedback approaches to empower and engage students: a sectoral approach in Ireland -- Restructuring the blended learning environment on campus for equity and opportunity through UDL -- Promoting digital access and inclusivity in open and distance learning in South Africa: a UDL approach -- UDL, online accessibility, and virtual reality: designing accessible and engaging online courses -- Conclusion: Universal Design for Learning: a global framework for realizing inclusive practice in higher education.
Includes bibliographic references and index.
Keywords: Inclusive education; Education, Higher